Impacts of Payment for Forest Ecosystem Services on Local livelihoods in A Luoi District, Thua Thien Hue Province, Viet Nam - Thuy, Pham Thu; Duong, Phuoc; Thuy, Le Thi Thanh (Forestry Faculty, Universitas Hasanuddin, 2022)
This paper analyses the impacts of the national Payment for Forest Environmental Services (PFES) policy in A Luoi district, Thua Thien Hue province, Viet Nam. There are mixed impacts of PFES in A Luoi district. While some surveyed households have experienced increases in income since PFES, for many other incomes have fallen. Our findings show PFES impacts on local communities and individuals are limited because most forest areas are managed by state agencies, leaving only 17.9% of PFES payments being channeled to these groups, while the rest goes to state government agencies and commune people’s committees. This disparity in PFES payments has further widened the income gap between state agencies and local households. PFES payments currently contribute little to household incomes, averaging only 2.64% of total earnings. PFES has little impact and additionality in advancing land tenure security and reducing natural forest product exploitation for generating income as impacts are similar to those found in non-PFES villages. PFES poverty reduction impacts vary from village to village, but in general, percentages of poor households receiving PFES payments range from 1% to 59%.